2019
DOI: 10.1371/journal.pone.0219617
|View full text |Cite
|
Sign up to set email alerts
|

Getting to intent: Are social norms influencing intentions to use modern contraception in the DRC?

Abstract: Meeting the reproductive health needs of women in post-conflict settings is a global health priority. In the Democratic Republic of the Congo, social norms perpetuate gender-based violence and contribute to low contraceptive use and high fertility. The Masculinité, Famille, et Foi (MFF) intervention is working with communities in Kinshasa to create normative environments supportive of modern contraception access and use. Our analysis uses survey data collected from 900 men and women in 17 community groups prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…Consistent with the literature, the study found that social norms that discourage premarital sex and contraceptive use are associated with lower levels of contraceptive use [ 1 , 24 , 34 36 ]. Our findings suggest that the effect of social norms on behavior is associated with ability.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with the literature, the study found that social norms that discourage premarital sex and contraceptive use are associated with lower levels of contraceptive use [ 1 , 24 , 34 36 ]. Our findings suggest that the effect of social norms on behavior is associated with ability.…”
Section: Discussionsupporting
confidence: 82%
“…Social norms can help explain reproductive health decisions, including the use of modern FP to space children [25][26][27]. According to social norms theory, individuals follow unwritten and unspoken rules that are shared amongst people in their reference group [25,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Social norms can help explain reproductive health decisions, including the use of modern FP to space children [25][26][27]. According to social norms theory, individuals follow unwritten and unspoken rules that are shared amongst people in their reference group [25,28,29]. These rules are mutual behavioral expectations and are sustained, amongst other things, by anticipation of approval or disapproval for, respectively, complying or not with them [30].…”
Section: Introductionmentioning
confidence: 99%
“…A study in India showed that descriptive norms around FP moderated the effects of spousal influence and interpersonal communication on married women's use of modern contraception (MC) (Rimal et al, 2015). Another study from the Democratic Republic of Congo found that injunctive FP norms among married women and descriptive FP norms among married men were associated with future intention to use MC (Costenbader et al, 2019). In Kenya and Ethiopia, a study by Dynes and colleagues highlighted that the alignment or divergence between injunctive norms and personal perceptions about the ideal number of sons influenced women's MC use (Dynes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Strategic behaviour change communication and interventions that go beyond shifting individual-level attitudes and behaviours have been a relatively recent focus of interventions in sub-Saharan Africa, including Nigeria (Costenbader et al, 2019;Ejembi et al, 2015). From 2009 to 2014, the Bill & Melinda Gates Foundation (BMGF) supported the Nigerian Urban Reproductive Health Initiative (NURHI) with the aim of increasing voluntary use of modern contraceptives among women ages 15-49 years in six large cities: Abuja, Ibadan, Ilorin, Kaduna, Benin and Zaira.…”
Section: Introductionmentioning
confidence: 99%